Novel Hybrid Spun Silk Yarn Developed from Eri and Mulberry Silks Under Industrial Level and Its Characterizations - Preetanat Kewcharoenwong; Kanokporn Sompornpailin (Journal of Natural Fibers, 2024)
To develop a novel hybrid spun silk yarn, the silk fibers have been analyzed in depth. This research aims to characterize the Mulberry and Eri silk fibers. The morphology of a single silk fiber was examined with an optical microscope and FESEM. The result of single-silk fiber properties showed that, Mulberry and Eri fibers have similar tensile strength (4.71 ± 0.98 and 4.93 ± 0.79 gram-force, respectively) but different in elongation percentage (13.43 ± 3.67 and 23.78 ± 4.90, respectively). Mulberry silk fibers are small, dense, compact, and non-porous, as for the Eri silk fibers, they are large, loose, and porous. Mulberry silk fibers have a smoother surface compared to Eri silk fibers. Mulberry and Eri silk fibers in different ratios were spun into silk yarn on an industrial scale, leading to the development of single and hybrid spun silk yarns. Under controlled yarn count and twist conditions, the hybrid silk yarns have an average tensile strength between that of single silk yarn. Adding more than 50% Mulberry silk fibers to spun silk yarn significantly reduced the percentage of yarn elongation. The synergistic effects of strength and elongation observed in Mulberry and Eri silk have resulted in novel yarns with new properties that can be applied in various textile industries.
Keywords: Silk-based biomaterials and applications; Silkworms and Sericulture Research